Stroop Testing Using a Hart Chart Format to Assess Sport-Related Concussion. - Clark, Joseph F.; Elgendy, Hagar (Optometry & Visual Performance, 2024)
Introduction: Pre-participation exams (PPE) in sports are vital in evaluating athlete safety and readiness for participation for the upcoming year. PPE ranges from evaluation of cardiovascular function to assessing for neurocognitive or neurological deficit. Sports-related concussion (SRC) baseline exams are a component of PPE. Computerized neurocognitive tests (CNTs) are widely used on different athletic performance platforms, although expense is a barrier, and many remain skeptical of their utility post-concussion. Neurological tests that can highlight impairment in executive functioning, short-term memory recall, complex task association, and vision perception and production are critical to consider for PPE. Stroop testing can be performed as a component of PPE and can serve as a baseline exam, as well as a sideline assessment to aid in identifying concussion impact on broader brain functions. In this paper, we combined saccadic eye movement, Stroop, and recall into a single, rapid, and costeffective assessment. Methods: A three-step Stroop panel was performed on 13 SRC patients and 167 PPE baselines. We examined the time it took to complete an 8x8 grid of Stroop words using a Hart chart saccadic eye movement task, plus a 10-word recall task. The three-step Stroop test set progressed in difficulty. The times it took to perform the tasks were assessed. Results: We found that the SRC patients performed significantly slower in performing the Stroop task, taking 84.5 ± 24.8 seconds compared to the PPE baseline of 62.3 ± 11.9 seconds (p= 0.000001). Both groups were similar in the 10-word recall of 4.0 ± 2.5 vs. 4.2 ± 1.7 correct out of ten. However, the 10 words had an undisclosed theme therein. When asked to identify the theme, the PPE baseline group recognized the theme 90% of the time compared to 31% for the SRC group (p=0.0000001). Discussion: In this paper, we present the methods for doing a three-step Stroop panel in support of using this exam as an objective tool to evaluate for concussions as a component of sideline concussion assessments. It is quantitative, cost-effective, and can be completed in about three minutes, revealing significant neurological function. The results support that the test can be used to assess memory, saccadic eye movement, and prefrontal cortex function. The regions of the brain assessed complement and extend the information that is obtained from other PPE baselines and neurologic tests post-SRC. We suggest that athletic trainers and other sports medical professionals consider using this Stroop panel in their sports concussion protocols as part of baseline and sideline assessments of concussions.